Physicochemical and Sensory Characteristics of Noni (Morinda citrifolia) Juice Drink with the Addition of Ginger and Lemongrass - Riska Rian Fauziah; Shinta Zahrotun Nisa; Jayus Jayus (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Noni (Morinda citrifolia) contains bioactive compounds, but it has an unpleasant odor caused by caproic acid. Due to essential oil compounds, ginger and lemongrass can be used to reduce the unpleasant aroma of noni fruit. This research aims to evaluate the effect of ginger and lemongrass with varying concentrations of noni juice on physicochemical and sensory characteristics noni drink. The study employed a completely randomized design with six treatments and four replications. Physicochemical data were analyzed using ANOVA and Duncan's post hoc test, while sensory data were analyzed using the Chi-Square test. Results indicated that the type of ginger and concentration of noni juice significantly influenced the chemical characteristics. A concentration of 10 ml of noni juice affected the physical and sensory properties of noni juice beverage, but this was not observed at a concentration of 20 ml. The best formula resulted from treatment with a concentration of 10 ml of noni juice and the addition of 10 ml of lemongrass, with an overall score of 4.13 (liked). This was attributed to the flavonoid content of 0.290 mgQE/ml, polyphenol content of 0.3500 mgGAE/ml, vitamin C content of 0.114 mg/ml, antioxidant activity of 17.65ml, as well as satisfactory scores for taste, aroma, and aftertaste. Keywords: Caproic acid, Drink, Noni, Spice.